A simple prescription for computing the stress-energy tensor - Accioly, A.; Azeredo, A. D.; deAragao, CML; Mukai, H. (Iop Publishing Ltd, 1997)
A non-variational technique for computing the stress-energy tensor is presented. The prescription is used, among other things, to obtain the correct field equations for Prasanna's highly nonlinear electrodynamics.